Experimental Study of the Effect of Plasma Cutting on the Tensile Strength of Materials "Fe" - I Wayan Suma Wibawa; I Ketut Suherman (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
The cutting process in plasma cutting begins with the formation of a pilot arc between the electrode and the workpiece as a result of the electrical ionization reaction of the highly conductive cutting gas. The gas is heated by the pilot arc until its temperature rises very high then the gas will be ionized and become a conductor of electricity. When the gas stream leaves the nozzle, the gas expands rapidly carrying the molten metal so that the cutting process continues. This plasma temperature can reach 33,000°C, approximately 10 times the temperature produced by the reaction of oxygen and acetylene. If this is related to the mechanical properties of the material, where the material has been heated it will result in changes in the mechanical properties of the material in the heating area/around the cutting plane. Tensile testing is the most widely used type of test because it is able to provide representative information on the mechanical behavior of the material. Seeing an incident like this, it is necessary to test the Effect of Plasma Cutting on the Tensile Strength of 'Fe' Materials through a tensile test. Several studies have shown that torch height, amperage and cutting speed can affect material properties. The best tool parameter settings are obtained at a travel speed of 500 mm/min, 75 amperes and a torch-material distance of 3 mm so that these settings are used as a reference in this study. In analyzing the data, the authors compare the results of plasma cutting testing with conventional cutting, in order to know the changes in mechanical properties that occur.